Some properties of q- close-to-convex functions - Özkan Uçar, Hatice Esra; Mert, Oya; POLATOĞLU, YAŞAR (My University, 2017)
Quantum calculus had been used first time by M.E.H.Ismail, E.Merkes and D.Steyr in the theory of univalent functions [5]. In this present paper we examine the subclass of univalent functions which is defined by quantum calculus.
Keywords: q− convex function; q− close to convex function; growth theorem; distortion theorem; coefficient inequality